Detection of drugs and their metabolites in oral fluid - White, Robert M. 1945-; Moore, Christine M. (Emerging issues in analytical chemistry, 2018)
Detection of Drugs and Their Metabolites in Oral Fluid presents the analytical chemistry methods used for the detection and quantification of drugs and their metabolites in human oral fluid. The authors summarize the state of the science, including its strengths, weaknesses, unmet methodological needs, and cutting-edge trends. This volume covers the salient aspects of oral fluid drug testing, including specimen collection and handling, initial testing, point of collection testing (POCT), specimen validity testing (SVT), and confirmatory and proficiency testing. Analytes discussed include amphetamines, cannabinoids, cocaine, opiates, phencyclidine, cannabimimetics, and miscellaneous drugs. This practical guide helps users turn knowledge into practice, moving logically from an outline of the problem, to the evaluation of the appropriateness of oral fluid as a test medium, and finally to a consideration of detection methods and their validation and employment